Statistical Description Of The Turbulent Round Jet Developing Region Along Its Centerline - Yaacob, Mohd Rusdy; Buchhave, Preben; Velte, Clara Marika (Penerbit Akademia Baru, 2019)
Due to the technical measurement difficulties, analysis on the developing region of a turbulent round jet has been omitted despite its vast significance in explaining the establishment of the fully developed counterpart. With a self-developed novel and sophisticated laser Doppler system that can accurately measure high turbulence intensity flow with high spatial resolution and dynamics range, a turbulent round jet is mapped in terms of statistical moments along the centerline throughout and beyond the developing region. About 25-30 jet exit diameters downstream, turbulence begins to approach the fully developed state where the mean velocity and variance develop in parallel in a seeming equilibrium. Turbulence intensity is consequently observed to initially increase before levelling out when approaching the fully developed state. The downstream development of the measured spatial energy spectra and second-order structure functions further support these observations in that they begin to develop the Kolmogorov characteristic-5/3 and 2/3 slopes in the inertial subrange within the downstream distance of 25-30 jet exit diameters. The dissipation can be to a reasonable approximation extracted from the third-order structure functions from about 20 jet exit diameters and further downstream. The results should be useful for development of analytic and numerical turbulence models.